Seroprevalence of varicella-zoster virus in the prevaccine era: A population-based study in Izmir, Turkey - Sükran Kose; Aliye Mandiracioglu; Süheyla Serin Senger; Yıldız Ulu; Gulsun Cavdar; Basak Gol; Ilhan Gurbuz; Senol Sariavci; Nese Nohutcu (Elsevier, 2013)
Summary: Purpose: To determine the population-based seroprevalence of varicella zoster virus (VZV) and related risk factors in Izmir. Materials and methods: A population-based household survey was conducted. A representative sample of the population older than 15 years of age was selected using multistage random sampling. A total of 2136 healthy persons participated in this cross-sectional study. The participants completed a questionnaire designed to collect data related to socio-demographic characteristics and risk factors. Blood samples were collected, and VZV-specific IgG was measured using an ELISA. Results: In total, 94.3% of individuals were seropositive for VZV. The difference between VZV seroprevalence in urban and rural populations was significant (OR: 2.6 (95% CI, 1.7-3.8)). No statistically significant differences in seropositivity were observed with respect to other sociodemographic characteristics. Conclusion: A large proportion of the participants were found to be immune to VZV. Keywords: IgG-specific test, Varicella zoster infection, Prevalence